Memahami Kekayaan Budaya dan Tradisi Suku Bali di Pulau Dewata yang Menakjubkan - Fahrurrozhi, Alfian; Kurnia, Heri (Jurnal Ilmu Sosial dan Budaya Indonesia, 2024)
This research is a literature study aimed at providing an in-depth understanding of the traditional customs and culture of the Balinese people, an indigenous ethnic group from the island of Bali, Indonesia. The Balinese are known for their rich cultural diversity, which includes their belief systems, traditional ceremonies, ngaben (cremation ceremonies), and unique way of life. This literature study will collect and analyze various sources of literature, including books, journal articles, and official documents relevant to Balinese traditions and culture. The collected data will be analyzed to identify patterns, developments, and key aspects of Balinese culture, as well as how their culture has interacted with modernization and social change. The findings from this literature study are expected to provide a deeper understanding of the cultural diversity of the Balinese people.